设z1、z2∈C,求证:|z1+z2|2+|z1-z2|2=2|z1|2+2|z2|2.
举一反三
- 1)z^2=z拔(2)z^2+|z|=0
- 【简答题】设 z 1 =4 + 3i , z 2 =2 - 3i ,计算 z 1 · z 2
- 若复数z 1=1+i ,z 2=3-i ,则z 1·z 2等于
- 设方程\(z^2+y^2+z^2 = 4z\)确定函数\(z=z(x,y)\),则\( { { {\partial ^2}z} \over {\partial {x^2}}} =\) A: \( { { { { (2 - z)}^2} + {x^2}} \over { { {(2+ z)}^3}}}\) B: \( { { { { (2 - z)}^2} + {x^2}} \over { { {(2 - z)}^3}}}\) C: \( { { { { (2 - z)}^2} -{x^2}} \over { { {(2 - z)}^3}}}\) D: \( { { { { (2 + z)}^2} + {x^2}} \over { { {(2 - z)}^3}}}\)
- 信号$x[n]=(n-3)u(n)$的Z变换结果是 A: $\frac{1}{z^2(z-1)^2}$ B: $\frac{1}{z^2(z-1)}$ C: $\frac{1}{z(z-1)^2}$ D: $\frac{1}{z^2(z+1)^2}$